Evaluation of tension-free vaginal tape and transobturator tape surgery performed in one year in terms of mesh erosion: Is the surgical method effective in mesh erosion? - Yıldız, Elif; Timur , Burcu (Journal of Surgery and Medicine, 2023)
Background/Aim: Mesh erosion is one of the feared complications in surgeries performed using mesh, and its frequency is increasing as more and more of these surgeries are performed. This study aims to evaluate transobturator tape (TOT) and tension-free vaginal tape (TVT) surgeries performed in the surgical treatment of stress urinary incontinence (SUI) in our clinic in terms of clinical results and mesh erosion. Methods: This study is a retrospective cohort study. The files of 50 patients who had SUI and underwent TOT and TVT surgery in our clinic between January 2022 and January 2023 were reviewed. Patients diagnosed with pure SUI and for whom surgery was performed were included in our study. The participants were divided into two groups: those who had TOT surgery and those who had TVT surgery. These groups were evaluated and compared in terms of mesh injury, mesh erosion, pelvic pain, dyspareunia symptoms, and urinary retention. The surgical data of patients, incidence of complications, pre- and postoperative incontinence impact questionnaires (IIQ-7) and the scores of the International Consultation on Incontinence Questionnaire Short Form (ICIQ-SF) were recorded. Results: The mean follow-up period of the participants was 8.96 (8.47) (range, 6-17 months). TVT surgery was performed on 13 participants and TOT surgery was performed on 37 patients. When the two groups were compared, there was no statistically significant difference in terms of age, body mass index (BMI), parity, menopausal status, duration of incontinence, preoperative IIQ-7 scores, and ICIQ-SF scores (P<0.05). There were no statistically significant differences between surgical durations, length of hospital stay, early surgical complications, postoperative 3rd month IIQ-7, and ICIQ-SF scores (P<0.05). Furthermore, no difference in the rates of mesh erosion and mesh-related complications between the two groups (P<0.05) was observed. Conclusion: TOT and TVT surgeries seem to be quite safe in terms of complications, as well as being satisfactory in terms of patient satisfaction. Although mesh-related complications can be frightening, the rate of regression is low with appropriate management. Our results show that both operations are safe with an acceptable complication rate when performed by surgeons who have experience with anti-incontinence procedures.